From the "feminization of agriculture" to gender equality - Doss, Cheryl R.; Qaisrani, Ayesha; Kosec, Katrina; Slavchevska, Vanya; Galiè, Alessandra; Kawarazuka, Nozomi (International Food Policy Research Institute, 2021)
The term “feminization of agriculture” is used to capture a wide range of gender dynamics and shifts in rural gender relations. Definitions range from the broadening and deepening of women’s involvement in agriculture (Lastarria-Cornhiel 2006) to the increase in rural women’s measured economic participation in agriculture and a reported visibility of women in agricultural activities (Deere 2005). The term may be used to imply an increase in women’s labor in agriculture, in women’s labor relative to that of men, or in women’s roles in agricultural decision-making. Broadly speaking, however, literature on the feminization of agriculture has challenged researchers and development practitioners to consider how changing rural landscapes are affecting women, especially where men are moving out of agriculture. These changes have impacts on women’s productive and reproductive workloads, both paid and unpaid, as well as their agency and decision-making, both within the farm and the household and in the community and a variety of institutions.